PERAN GURU DALAM MENCEGAH BULLYING DI SEKOLAH DASAR: MENCAPAI PENDIDIKAN BERKUALITAS YANG SEIRING DENGAN TUJUAN PEMBANGUNAN BERKELANJUTAN 4 - Nizmi, Yusnarida Eka Nizmi; Olivia, Yessi; Yulia , Rahmi; Takwa, Tuah Kalti; Hidayati, Umunnisa; Alby , Syahroni; Purwasandi, Purwasandi (LPPM, Universitas Muhammadiyah Riau, 2024)
Bullying in elementary schools is a widespread issue that significantly impacts students' mental health, social development, and academic performance. This study examines the crucial role of teachers in preventing bullying and explores its implications for achieving quality education in line with Sustainable Development Goal (SDG) number 4. Using a qualitative descriptive methodology, data were collected through questionnaires administered to students, supported by secondary data analysis from relevant literature and legal frameworks. The findings indicate that students' understanding of bullying makes them vulnerable to this practice. Proactive involvement of teachers in creating a safe and inclusive learning environment is essential to reducing incidents of bullying. Furthermore, this study highlights the importance of legal regulations, such as the Child Protection Law, in providing a framework for teachers to effectively fulfill their responsibilities. In this community service activity, students from SD 12 Lubuk Garam, Siak Kecil, were provided with knowledge about bullying and its effects on mental health. The research results show that teachers must transform from traditional educators into active agents of social change, promoting a culture of respect and safety within schools. This study encourages the enhancement of legal literacy among educators and the implementation of ongoing professional development programs focused on bullying prevention strategies. By equipping teachers with the necessary tools and knowledge, schools can create a more supportive atmosphere conducive to quality education and the overall well-being of students. Keywords: Bullying, Elementary School, Role of The Teachers, Sustainable Development Goal